Gene Expression Profiles of Human Mesenchymal Stromal Cells Derived from Wharton’s Jelly and Amniotic Membrane before and after Osteo-Induction Using NanoString Platform - Vun Vun Hiew; Haselamirrah Mohd Akhir; Peik Lin Teoh (Current Issues in Molecular Biology, 2022)
The use of perinatal mesenchymal stem cells (MSCs) in bone tissue regeneration and engineering to substitute bone marrow MSCs has drawn great interest due to their high yield, ease of procurement, multilineage differentiation potential and lack of ethical concerns. Although amniotic membrane (AM) and Wharton’s jelly (WJ)-derived MSCs have been widely shown to possess osteogenic differentiation potential, the intrinsic properties determining their osteogenic capacity remain unclear. Here, we compared gene expression profiles of AM- and WJ-MSCs at basal and osteogenic conditions by using the NanoString Stem Cell Panel containing regulatory genes associated with stemness, self-renewal, Wnt, Notch and Hedgehog signalling pathways. At basal condition, WJ-MSCs displayed higher expression in most genes regardless of their functional roles in self-renewal, adhesion, or differentiation signalling pathways. After osteo-induction, elevated expression of self-renewal genes ADAR and PAFAH1B1 was observed in AM-MSCs, while stemness genes MME and ALDH1A1 were upregulated in WJ-MSC. Both MSCs showed differences in genes associated with ligands, receptors and ubiquitin ligases of the Notch pathway. In addition, further evidence was demonstrated in some signalling molecules including CTBPs, protein kinases, phosphatases, RHOA, RAC1. Downstream targets HES1 and JUN especially showed higher expression in non-induced WJ-MSCs. Hedgehog genes initially expressed in both MSCs were downregulated in WJ-MSCs during osteogenesis. This study has provided insights into the intrinsic biological differences that may lead to their discrimination in therapeutic intervention.